Recombinant expression library of Pyrococcus furiosus constructed by high-throughput cloning: a useful tool for functional and structural genomics - Yuan, Hui; Peng, Li; Han, Zhong; Xie, Juan-Juan; Liu, Xi-Peng (Frontiers in Microbiology, 2015)
Hyperthermophile Pyrococcus furiosus grows optimally near 100°C and is an important resource of many industrial and molecular biological enzymes. To study the structure and function of Pyrococcus furiosus proteins at whole genome level, we constructed expression plasmids of each Pyrococcus furiosus gene using a ligase-independent cloning method, which was based on amplifying target gene and vector by PCR using phosphorothioate-modified primers and digesting PCR products by λ exonuclease. Our cloning method had a positive clone percentage of ≥ 80% in 96-well plate cloning format. Small-scale expression experiment showed that 55 out of 80 genes were efficiently expressed in Escherichia coli Strain Rosetta 2(DE3)pLysS. In summary, this recombinant expression library of Pyrococcus furiosus provides a platform for functional and structural studies, as well as developing novel industrial enzymes. Our cloning scheme is adaptable to constructing recombinant expression library of other sequenced organisms.